Key concepts of agroecology science. A systematic review (2016)
ABSTRACT : A systematic review was conducted with the objective of determining the key concepts that are currently used in theoretical work in agroecology. They were obtained from titles and keywords of theoretical articles and books that included the term agroecology in the title. Fifteen terms with occurrences higher than three were obtained. They show that agroecology revolves around the concept of integral sustainability, and that there is agreement on neither its object of study nor goal. As a result, most key concepts concern the object of study or the goal of agroecology. Other key concepts are food sovereignty, agriculture, ecofeminism, climate change, family farming, and social movements.